Biotechnology, agriculture, and food security in Southern Africa - Omamo, Steven Were; von Grebmer, Klaus (International Food Policy Research Institute, 2005)
Biotechnology disputes fall into the ever-expanding category of policy disputes characterized by multidimensionality and complexity. By their very nature, these disputes are centered around politically charged issues of allocation of rights to resources, as well as distribution of the benefits and costs of technological change. They typically involve a high degree of scientific uncertainty, long time horizons, and decisionmaking at multiple jurisdictional levels. Such disputes are therefore likely to pose exacting challenges. They involve a wide range of political, economic, social, and scientific considerations. Their satisfactory resolution therefore requires multistakeholder participation in a process of finding and maintaining a dynamic balance between political and technical priorities. In this process civil society can provide much of the expertise and creative thinking that is required to identify needs, generate innovative policy options, and implement agreements while governments retain their preeminent functions of ultimate decisionmaking.